Learning History Through Augmented Reality - Bayu Dirgantoro (Journal of Games, Game Art, and Gamification, 2021)
History has been adapted as a compulsory subject since 1931 alongside math and science. However, learning history in Indonesia could be a challenge since Indonesia placed in the second lowest of literature behaviour. For the past decades, educators have been implementing the term of in class edutainment and gamification. One of the forms of edutainment could be accomplished by Augmented Reality. This project is conducted to provide an alternative learning tool in history learning, especially for elementary school students who tend to have a negative paradigm that learning history means reading textbooks. In addition, the function of Augmented Reality will be beneficial to students and teachers in order to support multiple learning styles without losing its substance as it is based on the K13 curriculum